2015
DOI: 10.15434/kssh.2015.28.3.150
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting MERS-related Health Behaviors among Male High School Students

Abstract: Purpose: The purpose of the study was to survey male high school students on their MERS(Middle East Respiratory Syndrome)-related knowledge, risk perception, and health behaviors and to identify the factors affecting health behaviors during the MERS outbreak in Korea. Methods: The subjects in this study were 144 students in a male high school. Data were collected through self-reported questionnaires in July, 2015. The collected data were analyzed by ANOVA, Pearson's correlation and multiple regression using SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…Moreover, we found that the higher the knowledge of individuals, the higher their perceived risk of MERS. Similarly, Choi et al [ 12 ] found a positive relationship between knowledge and risk perception. However, these findings contradicted Yang and Cho’s [ 3 ] findings in which the level of knowledge about MERS was not associated with risk perception.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, we found that the higher the knowledge of individuals, the higher their perceived risk of MERS. Similarly, Choi et al [ 12 ] found a positive relationship between knowledge and risk perception. However, these findings contradicted Yang and Cho’s [ 3 ] findings in which the level of knowledge about MERS was not associated with risk perception.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, Lee et al [ 7 ] reported that the infection sensitivity of community residents during the MERS outbreak in Korea correlated with gender, age, occupation, and health behaviors. Based on a survey of male high-school students, Choi et al [ 12 ] revealed that their risk perception score was 1.8 on a 4-point scale. Moreover, there was a positive correlation between knowledge, risk perception, and health behaviors.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…. 남자 고교생은 메르스 관련 지식 이 높을수록 메르스 예방행위를 잘하는 것으로 나타났다 9) . Items Mean±SD Transmission of MERS-CoV infection can be prevented by using universal precautions given by CDC, WHO etc.…”
unclassified
“…This is a tool that measures the prevention of infection and the promotion of long-term health care in the COVID-19 pandemic. It was revised based on the guidelines of Choi (2015), CDSCH (2020), and WHO (2020) [44][45][46].…”
Section: Health Promotion Behaviorsmentioning
confidence: 99%